2017
DOI: 10.1111/sdi.12637
|View full text |Cite
|
Sign up to set email alerts
|

Predicting in a predicament: Stroke and hemorrhage risk prediction in dialysis patients with atrial fibrillation

Abstract: Whether to anticoagulate dialysis patients with atrial fibrillation is a common clinical dilemma with limited high-quality data to inform decision-making. While the efficacy and safety of anticoagulation for stroke prevention in dialysis patients with atrial fibrillation has long been debated and remains unclear, the more upstream issue of stroke risk assessment from atrial fibrillation has received relatively little attention.In the general population, a handful of risk scores to help predict stroke and hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 112 publications
(147 reference statements)
1
11
0
2
Order By: Relevance
“…Failure to take these risk factors into account, as well as assigning different weights of conventional risk factors in assembling an overall risk for ischemic stroke may explain why the CHA 2 DS 2 -VASc, the most commonly used stroke risk score in the general population, has limited validation in the MHD population. A literature review on stroke risk stratification by CHA 2 DS 2 -VASc in the MHD populations reported c-statistics of less than 0.70 in almost all studies [ 26 ] which are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Failure to take these risk factors into account, as well as assigning different weights of conventional risk factors in assembling an overall risk for ischemic stroke may explain why the CHA 2 DS 2 -VASc, the most commonly used stroke risk score in the general population, has limited validation in the MHD population. A literature review on stroke risk stratification by CHA 2 DS 2 -VASc in the MHD populations reported c-statistics of less than 0.70 in almost all studies [ 26 ] which are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Некоторые исследователи считают, что проблема ФП у больных, находящихся на диализе, не находит должного внимания в плане выбора шкал для оценки риска развития тромбоэмболических осложнений и кровотечений [23]. Так, в общей популяции больных с ФП для оценки разви-тия риска инсульта и кровотечений при назначении АКТ широко используются в клинической практике шкалы, такие как CHA 2 DS 2 -VASC, HAS-BLED.…”
Section: прогноз у больных с фп и терминальной стадией хбп находящихunclassified
“…Older age, male sex, diabetes, and hypertension were independent risk factors for ischemic and hemorrhagic strokes in patients undergoing dialysis [ 29 ]. Until now, the preventive effect of anticoagulants on the risk of stroke was not evident, and the prerequisite issue of stroke risk assessment from atrial fibrillation in patients undergoing dialysis has rarely been discussed [ 30 , 31 ]. In our study, a high incidence of stroke was noted in the SC cohort, and SC was associated with an increased risk of stroke regardless of sex, age, dialysis modality, or comorbidities ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%